Tuberculous Liver Abscess in an Immunocompetent Patient: a Case Report - Shokouhi, Shervin (Tanaffos, 2014)
INTRODUCTION: Tuberculous or tubercular liver abscess (TLA) is a rare manifestation of extrapulmonary tuberculosis (TB) and it should be considered in the differential diagnosis of mass or cystic lesions of the liver especially in a high TB prevalence country like Iran. CASE PRESENTATION: We report an immunocompetent 48 year-old woman with TLA and peritoneal infection. Although hepatic TLA is very rare, it should be considered in the differential diagnosis of mass or cystic lesions of the liver especially in a high TB prevalence country.